2014
DOI: 10.1007/s10517-014-2612-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Simvastatin in Patients with Chronic Heart Failure

Abstract: Proinflammatory markers were evaluated in patients with chronic heart failure of ischemic origin and essential hypertension with preserved left-ventricular ejection fraction before and after a 6-month course of simvastatin therapy (20 mg/day). The study was carried out in 125 patients with diastolic dysfunction manifested as impaired relaxation and pseudonormalization. The main group received standard therapy for chronic heart failure and simvastatin, controls received only standard therapy. In addition, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Statins (3-hydroxy-3-methylglutaryl-CoA reductase inhibitors) are a major class of drugs for treating hypercholesterolaemia (Gbelcova et al, 2013). Alongside hypolipidaemic effects, statins exert antiinflammatory (Pinchuk et al, 2014), antioxidative (Cao et al, 2017), and anti-cancer effects (Sleijfer, van der Gaast, Planting, Stoter, & Verweij, 2005), and they also participate in endothelial regulation and influence cell autophagy and apoptosis (Hwang et al, 2015). However, numerous questions regarding the role of simvastatin in the heart remain unanswered and require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Statins (3-hydroxy-3-methylglutaryl-CoA reductase inhibitors) are a major class of drugs for treating hypercholesterolaemia (Gbelcova et al, 2013). Alongside hypolipidaemic effects, statins exert antiinflammatory (Pinchuk et al, 2014), antioxidative (Cao et al, 2017), and anti-cancer effects (Sleijfer, van der Gaast, Planting, Stoter, & Verweij, 2005), and they also participate in endothelial regulation and influence cell autophagy and apoptosis (Hwang et al, 2015). However, numerous questions regarding the role of simvastatin in the heart remain unanswered and require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Simvastatin is an angiotensin II receptor inhibitor and is commonly used to treat hyperlipidemia and hypertension. Clinical observation found that taking simvastatin for 20 days significantly reduces the levels of proinflammatory markers interleukin-6 and C-reactive protein in patients with chronic HF 144 . It also induces lipid droplet accumulation, provides energy for maintaining mitochondrial function, promotes mitochondrial autophagy and phagocytosis, and inhibits mitochondrial damage and cardiomyocyte apoptosis 145 .…”
Section: Potential Drugs For Reducing Hf By Regulating Energy Metabolismmentioning
confidence: 98%
“…In a population of 3124 HFpEF patients, Nochioka et al demonstrated that statins could be associated with reduced all‐cause and non‐cardiovascular mortality rates. Another small study documented that statin therapy could reduce inflammatory biomarkers with beneficial effects on diastolic pattern and myocardial relaxation …”
Section: Biomarkers In Heart Failure With Preserved Ejection Fractionmentioning
confidence: 99%